ANALISIS POTENSI EKSPOR INDONESIA TERHADAP NEGARA ASEAN DENGAN PEMANFAATAN PERJANJIAN MASYARAKAT EKONOMI ASEAN (MEA) - Bambang Septiawan; Gesta Amaria Sabila; Yufi Priyo Sutanto (AKUNTABILITAS: Jurnal Ilmiah Ilmu-Ilmu Ekonomi, 2023)
Indonesia is a country that has the largest population and the largest area in ASEAN. This advantage can be a potential for Indonesia to move the wheels of the economy through international trade. The purpose of this study is to analyze Indonesia's export potential to ASEAN countries with the existence of the Asean Economic Community (AEC) agreement. Research using literature study method. This method focuses on using valid and reliable data. Based on the results of data analysis, there is no significant difference regarding the total value of Indonesia's exports to ASEAN countries either before or after the ASEAN Economic Community (AEC) agreement was enforced. It is felt that there is a need for diversification of trade products, due to the minimal trade rotation between ASEAN members allegedly because they have similar commodities and even tend to be similar.